Features of the inflation targeting strategy in Kazakhstan - Romazanov, Zh.K.; Niyazov, T.J.; Karipov, T.A.; Yskak, N.P.; Kazhmukhametova А.А. (BUKETOV BUSINESS REVIEW, 2024)
Object: The article discusses issues related to the monetary policy pursued by the National Bank of Kazakhstan and its impact on the development of the country’s economy. The applied monetary policy is aimed at combating inflation and does not take into account the general economic interests of the country, without ensuring economic growth based on expanded reproduction of goods. Methods: In the course of the work, classical techniques and methods of information processing were used: grouping, classification, logical modeling, generalization and systematization, synthesis, systematic approach, comparison, extrapolation of trends. A review of foreign and domestic scientific papers on the problem of inflation targeting made it possible to study the purpose, essence and methods of such monetary policy, to identify its advantages and disadvantages in relation to the economies of developing countries. Findings: The compression of the money supply in the country, as a result of the fight against inflation, leads to an under-crediting of the real sector of the economy and a reduction in investment in industry. With a sufficiently long period of implementation of such a monetary policy, the country is drawn into a stagflationary trap, in which economic growth is declining, inflation and unemployment are rising. Conclusions: The main consequence of such a monetary policy is the failure to achieve the goals of diversifying the country’s economy and avoiding dependence on raw materials. Therefore, the task of this study is to identify the causes and consequences of the implementation of the monetary policy of the National Bank.